Pertanggungjawaban Perdata Perseroan Terbatas Global Elektrik terhadap Pengguna Lampu Visalux Light Emitting Diode di Kota Jambi - Nur Fauzia; Abdul Hariss (Universitas Batanghari Jambi, 2026)
This study examines the civil liability of Global Elektrik Limited Liability Company towards Visalux Light Emitting Diode Lamp Users in Jambi City. In the sales and purchase agreement between PT. Global Elektrik through 125 stores in Jambi City to customers, there are several complaints that arise regarding Visalux Light Emitting Diode lamp products that are claimed not to function properly. For this reason, further research is needed regarding the form of civil liability of PT. Global Elektrik to Users, what are the obstacles in implementing the civil liability and how to resolve the obstacles faced in implementing the civil liability of PT. Global Elektrik. The method in this study is a sociological juridical method with a descriptive study approach and a social approach. The research materials are in the form of primary, secondary, and tertiary legal materials with data collection techniques using interview techniques and document studies. Regarding the research in question, it is known that PT Global Elektrik is responsible for hidden defects in the lamps. The obstacles faced are related to proving the existence of hidden defects in the Visalux Light Emitting Diode lamps. Meanwhile, the form of responsibility from PT Global Elektrik is providing a guarantee, making replacements, and refunding the purchase price of the lamps, as well as providing souvenirs or compensation for users.